2019
DOI: 10.1016/j.icarus.2019.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and coordination number of compressed dust aggregates

Abstract: Understanding the heat transfer mechanism within dust aggregates is of great importance for many subjects in planetary science. We calculated the coordination number and the thermal conductivity through the solid network of compressed dust aggregates. We found a simple relationship between the coordination number and the filling factor and revealed that the thermal conductivity through the solid network of aggregates is represented by a power-law function of the filling factor and the coordination number.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…According to empirical relationships between the coordination number and the packing fraction for aggregates of spherical particles [15,16,26] (Fig. 7), the packing fraction of ~0.3 corresponds to an average coordination number of ~3-5, which is consistent with numerical results [14].…”
Section: Resultssupporting
confidence: 84%
“…According to empirical relationships between the coordination number and the packing fraction for aggregates of spherical particles [15,16,26] (Fig. 7), the packing fraction of ~0.3 corresponds to an average coordination number of ~3-5, which is consistent with numerical results [14].…”
Section: Resultssupporting
confidence: 84%
“…(D.4) Therefore, F Ph /F D is independent of a for the case of a < l m , while F Ph /F D is inversely proportional to the square of the particle radius for the case of a > l m This means that the radial drift of cm-sized compact pebbles could not be prevented by photophoresis itself, although the radial drift would be stopped because the pressure maximum formed at the light barrier. We note, however, that the thermal conductivity of dust aggregates is exceedingly lower than that of compact dust particles (e.g., Arakawa et al 2017Arakawa et al , 2019, and the radial drift of aggregated pebbles might be stopped by photophoresis, even if their radius is larger than the mean free path of the gas molecules. Temperature T [K] p = 10 0 dyn cm -2 p = 10 2 dyn cm -2 p = 10 4 dyn cm -2 p = 10 6 dyn cm -2 fitting 10 -5 10 -4 10 -3 10 -2 10 -1 10 0 10 1 10 2 10 2 10 3 where c p = 10 7 erg g −1 K −1 is the specific heat (e.g., Ciesla et al 2004).…”
Section: Appendix D: Mean Free Path Of Gas Moleculesmentioning
confidence: 73%
“…The aggregation of monomers formed with a larger geometric diameter and wider distribution as the increase in the volume fraction, which means that the polydisperse of coagulation is higher with the denser system. Teichmann and Van also found that the coordination number (i.e., the average number of contacts per monomer) increases with the compression of aggregates [41]. Figure 10 shows the power-law relationship between the radius of gyrations a number of monomers in each aggregate under stable conditions.…”
Section: Cluster Analysis Of Collision Particlesmentioning
confidence: 89%